2014
DOI: 10.31899/rh10.1020
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and newborn health behaviors in rural Uttar Pradesh: Findings from learning phase baseline survey 2013

Abstract: The Population Council confronts critical health and development issues from stopping the spread of HIV to improving reproductive health and ensuring that young people lead full and productive lives. Through biomedical, social science, and public health research in 50 countries, we work with our partners to deliver solutions that lead to more effective policies, programs and technologies that improve lives around the world. Established in 1952 and headquartered in New York, the Council is a non-governmental, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The selection of districts was based on geographical diversity and duration of the existence of SHGs. A total of 15 blocks were selected with at least two from each of the districts [18]. This study protocol was reviewed and approved by the Institutional Review Board of the Population Council, New York.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of districts was based on geographical diversity and duration of the existence of SHGs. A total of 15 blocks were selected with at least two from each of the districts [18]. This study protocol was reviewed and approved by the Institutional Review Board of the Population Council, New York.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics were used to present socio-economic, demographic and household characteristics for all households, and also for SHG and non-SHG households separately. Socio-economic status of households, wealth index, was computed through principal component analysis using the variables of household amenities, assets and durables [18].…”
Section: Methodsmentioning
confidence: 99%
“…The peer effect in SHG groups other than access to credit, for example, was recently attributed by a study in India that showed increased school enrolment of members children as compared to non-members [48]. This is pertinent in the rural UP context where almost 70 per cent of women lack access to traditional sources of information through the media (television, radio, newspaper) coupled with gaps in the quality of health information provided through the public health system [49]. The membership appeal in SHGs for women and mothers can thus be understood.…”
Section: Maternal Health Indicators and Shg Membership And Durationmentioning
confidence: 99%
“…As per the Sample Registration Survey 2013 (SRS, 2013), the estimates of MMR and IMR of UP are at 292 per 100,000 live births and 50 per 1000 live births respectively. Current analyses are performed using data from the baseline learning phase of the Uttar Pradesh Community Mobilization (UPCM) Project [ 8 ] (the details of which are described below) to better understand the experiences of integrating FLWs into health systems to improve maternal and newborn outcomes in a setting such as UP.…”
Section: Introductionmentioning
confidence: 99%